2021
DOI: 10.3390/s21237873
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Carbon Nanofiber Mats for Prospective Single Photon Avalanche Diode (SPAD) Sensing Applications

Abstract: Electrospinning enables simple and cost-effective production of magnetic nanofibers by adding nanoparticles to a polymer solution. In order to increase the electrical conductivity of such nanofibers, the carbonization process is crucial. In this study, the chemical and morphological properties of magnetic nanofiber mats prepared from polyacrylonitrile (PAN)/magnetite were investigated. In our previous studies, PAN/magnetite nanofiber mats were carbonized at 500 °C, 600 °C, and 800 °C. Here, PAN/magnetite nanof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 93 publications
(193 reference statements)
0
3
0
Order By: Relevance
“…Our previous studies have shown that poly(acrylonitrile) (PAN) nanofiber mats with magnetite (20 wt%) or nickel ferrite nanoparticles (25 wt% in the spinning solution) electro-spun by the needleless machine "Nanospider Lab", as in this study, showed beads in which the magnetic nanoparticles agglomerated [24,25]. As in the previous study, mechanical separation by ultrasonic treatment was used in our material system for preparation of the electrospinning solution [5,26].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Our previous studies have shown that poly(acrylonitrile) (PAN) nanofiber mats with magnetite (20 wt%) or nickel ferrite nanoparticles (25 wt% in the spinning solution) electro-spun by the needleless machine "Nanospider Lab", as in this study, showed beads in which the magnetic nanoparticles agglomerated [24,25]. As in the previous study, mechanical separation by ultrasonic treatment was used in our material system for preparation of the electrospinning solution [5,26].…”
Section: Introductionmentioning
confidence: 71%
“…The individual MNFs look significantly thicker (Figure 3c) compared to nanofiber mats in Figure 3a CLSM images provided the first insight and SEM micrographs were used for a deeper investigation (see Figure 5). Here, nanofiber mats with 16 wt% PAN are discussed in more detail because according to our previous studies, 16% PAN in the electrospinning solution and 80 kV voltage were used as the best electrospinning parameters for producing uniform, well-separated nanofibers [5,16,17,26]. The morphology of the MNFs is shown in Figure 5 by SEM micrographs at 5000× magnification.…”
Section: Resultsmentioning
confidence: 99%
“…This step contributes to the formation of a sp 2 carbon structure. The stabilization process strengthens the fibers by giving them a more robust structure and increasing their thermal stability [88]. It also prevents the precursor fibers from melting or losing their shape during the subsequent carbonization process.…”
Section: Stabilization and Carbonization Process Of Nanofibersmentioning
confidence: 99%
“…They have great potential in this field due to the unique physical and chemical properties of electrospun nanofibers, including their networks of nanoporous and microporous structures, their large specific surface-to-volume ratio, tunable porosity, and flexible surface functional-ity [38][39][40][41][42][43]. Electrospinning is a very simple, cost-effective, and environmentally friendly process for producing nanofibers from various polymers [44] and even ceramics [45]. In addition, electrospun magnetic nanofiber mats can be produced from bio-or natural polymer solutions with magnetic additives [46].…”
Section: Introductionmentioning
confidence: 99%